Understanding the Complex Relationship Between Good Governance and Economic Growth in Indonesia During the Reform Era - Asmara, Anugerah Yuka; Sumarwono, Rudiarto (UI Scholars Hub, 2021)
Economic growth in Indonesia had fluctuated during the reform era which began in 1998 due to the political condition of Indonesia. For many developing countries like Indonesia in this case, economic growth and governance becomes an interesting issue to be discussed. In one hand, scholars argue that practice of good governance principles as main requisites to accelerate national economic growth. Otherwise, scholars finds that few developing countries can promote national economic growth rapidly without implementing good governance practice at first. ,Case in Indonesia practice of good governance principles during the reformera shows increasing results. This study is conducted through literature review by using historical institutionalism analysis aimed to describe relationship economic growth and good governance throughout the Indonesian reform era. This paper finds that economic growth in Indonesia during the reform era was the result of a variety of independent factors, not a single factor.